The Concept of Love and The Basis of Its Doctrines Between Maqamat and Haal - Abdul Wachid Bambang Suharto (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2021)
Basically, Sufism is the spiritual "path" of the Sufis to achieve eternal happiness. Sufism's orientation is a noble love for Allah SWT. Throughout the history of Sufism, love (isyq) for the Sufis became an ideology as well as a method of spiritual purification. Love restores the essence of human life to the Qur'an and Allah alone so that it has an essential accentuation of spirituality. This research uses a qualitative approach. This type of research is a library of research by collecting and documenting all the data relating to Sufism, love, and teachings, especially in the Qur'an and some Sufi figures. The results of this study revealed the love of a wayfarer (Salik) obtained through the long spiritual journey (suluk) in his life. It includes the prayer and the foundation of his stages (maqaamat), such as repentance (tawba), renunciation (zuhd), patience (ṣabr), gratitude (syukr), and watchfulness (wara'), and his basic doctrines such as fear (khauf) and hope (raja’).